Age-Dependent Regulation of Notch Family Members in the Neuronal Stem Cell Niches of the Short-Lived Killifish Nothobranchius furzeri - Bagnoli, Sara; Terzibasi Tozzini, Eva (Frontiers in Cell and Developmental Biology, 2021)
Background: The annual killifish Nothobranchius furzeri is a new experimental model organism in Biology, since it represents the vertebrate species with the shortest captive lifespan, and also shows the fastest maturation and senescence recorded in the laboratory. Here, we use this model to investigate the age-dependent decay of neurogenesis in the telencephalon (brain region sharing the same embryonic origin with the mammalian adult niches), focusing on the expression of the Notch pathway genes Results: We observed that the major ligands/receptors of the pathway showed a negative correlation with age, indicating age-dependent down-regulation of the Notch pathway. Moreover, expression of notch1a was clearly limited to active neurogenic niches and declines during aging, without changing its regional patterning. Expression of notch3 is not visibly influenced by aging. Conclusions: Both expression pattern and regulation differ between notch1a and notch3, with the former being limited to mitotically-active regions and reduced by aging, and the latter being present in all cells with a neurogenic potential, irrespective of the level of their actual mitotic activity, and so is less influenced by age. This finally suggests a possible differential role of the two receptors in the regulation of the niches proliferative potential throughout the entire fish life.